Sharing Mono-Institutional Experience of Treating Pancreatic Cancer with Stereotactic Body Radiation Therapy (SBRT) - Asmara Waheed; Shannah Murland; Eugene Yip; Amr Heikal; Sunita Ghosh; Aswin Abraham; Kim Paulson; Keith Tankel; Nawaid Usmani; Diane Severin; Clarence Wong; Kurian Joseph (Current Oncology)
Background: Stereotactic body radiotherapy (SBRT) is an evolving treatment for the local management of pancreatic cancer (PC). The main purpose of this study is to report our initial experience in terms of local control (LC) and toxicity for PC patients treated with SBRT. Methods: We conducted a retrospective review of patients treated with SBRT using abdominal compression (AC) or an end-expiratory breath-holding (EEBH) technique. The median prescribed dose was 35 Gy, delivered in five fractions. Toxicities were recorded using Common Terminology Criteria for Adverse Events (CTCAE) v5.0, and survival was estimated using the Kaplan–Meier method. Results: From 2017 to 2023, 17 PC patients were offered SBRT. Their median age was 69 years. The median follow-up from the date of diagnosis was 22.37 months. The overall survival (OS) was 94% at 1 year and 60.9% at 2 years. The progression-free survival (PFS) was 63.1% at 6 months and 56.1% at 9 months. The median OS was 26.3 months, and the median PFS was 20.6 months. The 6-month and 1-year LC rates were 71% and 50.8%, respectively. Conclusion: We are successful in implementing the SBRT program at our centre. SBRT appears to be a promising treatment option for achieving LC with limited acute toxicities.